2022
DOI: 10.3390/ijms23105450
|View full text |Cite
|
Sign up to set email alerts
|

Structural Abnormalities of the Optic Nerve and Retina in Huntington’s Disease Pre-Clinical and Clinical Settings

Abstract: Huntington’s disease (HD) is a fatal neurodegenerative disorder caused by a polyglutamine expansion in the huntingtin protein. HD-related pathological remodelling has been reported in HD mouse models and HD carriers. In this study, we studied structural abnormalities in the optic nerve by employing Spectral Domain Optical Coherence Tomography (SD-OCT) in pre-symptomatic HD carriers of Caucasian origin. Transmission Electron Microscopy (TEM) was used to investigate ultrastructural changes in the optic nerve of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…The attenuated GCIPL thickness found in our study confirms prior work that identified thinning in both the ganglion cell layer and the inner plexiform layer in individuals with [41,42]. In contrast, our study focused on individuals who were genetically positive and in the prodromal or motor manifest disease stage, and therefore had a more advanced form of HD than the 2 prior which could account for the differences seen in GCIPL thickness.…”
Section: Plos Onesupporting
confidence: 83%
See 3 more Smart Citations
“…The attenuated GCIPL thickness found in our study confirms prior work that identified thinning in both the ganglion cell layer and the inner plexiform layer in individuals with [41,42]. In contrast, our study focused on individuals who were genetically positive and in the prodromal or motor manifest disease stage, and therefore had a more advanced form of HD than the 2 prior which could account for the differences seen in GCIPL thickness.…”
Section: Plos Onesupporting
confidence: 83%
“…HD[40]. Interestingly, GCIPL attenuation was not found by Mazur-Michałek et al and Schmid et al[41,42]. Both papers had slightly different cohorts than our study, with Mazur-Michałek et al studying asymptomatic individuals who were genetically positive for HD and Schmid et al studying both individuals who were genetically positive and in the asymptomatic or the prodromal disease stage…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…Saccade deficits have been well documented in premanifest and manifest HD patients, and are considered potential biomarkers of disease development and progression [5][6][7][8][9][10][11][12][13][14][15][16][17]. The structural abnormalities of the optic nerve and retina displayed in pre-symptomatic HD carriers could be other potential biomarkers that would be of great interest in HD gene therapies [18]. Recently, impaired smooth pursuit of eye movement was described in an atypical motor presentation of HD with dominant dystonic symptoms at the onset of the disease [19].…”
Section: Introductionmentioning
confidence: 99%